Murder in a cup - Elliott, Lauren (Elliott, Lauren. Crystals & CuriosiTEAS mysteries., 2024)
"Self-taught "seer" Shay has much to learn as autumn hits the quaint coastal town of Bray Harbor. Since attempting the art of blending herbs at her popular shop, Crystals & CuriosiTeas, she's set on growing ingredients in the mysterious greenhouse on the second floor--if only she can separate the medicinal plants from the deadly ones. Her new skills are put to the test when she meets pub owner and ex-detective Liam Madigan's Gran. A psychic from Ireland known for interpreting tea leaves and people, Gran encourages Shay to build upon her natural talents and hold her own group reading . . .Despite Shay's reservations about putting herself in the spotlight, the evening goes off without a hitch. At least, until she does a reading and a customer goes from chatty to dead in a flash, poisoned after sipping a toxic substance recently grown in the greenhouse. Worse, Shay's assistant is suspected of intentionally serving the lethal brew and committing cold-blooded murder. Now, aided only by Liam and her dog Spirit, Shay must exonerate her employee and save the future of Crystals & CuriosiTeas. But when clues start lining up like leaves in a teacup, she'll need to understand the signs right in front of her to catch the manipulative murderer before it's too late . . ." --